The World Bank Macro-Fiscal Model Technical Description - Burns, Andrew (World Bank, Washington, DC, 2019)
This paper outlines the structure and economic foundation of the World Bank's macroeconomic and fiscal model (MFMod). MFMod consists of individual country models for 181 countries. The models are used by country economists within the World Bank's Macroeconomics, Trade and Investment Global Practice to (i) generate country forecasts and (ii) simulate various policies. Each model has a similar structure and functional form, with variation reflecting data availability and economic specialization (notably for oil exporters). Although the functional forms are similar, the parameters are country specific and estimated at the country level. Forecasts across countries are live-linked, with the export market growth of each country calculated as a trade-weighted average of imports of each of its trading partners. Remittance inflows and outflows are balanced across countries through a similar mechanism. Other cross-country linkages come through the real effective exchange rate and export and import prices, which are a function of world commodity prices and local cost considerations.